Deteksi Dini Emosi dan Perilaku Siswa Menggunakan SDQ (Strength and Difficulties Questionnaire) - Nurhayati (LPPI Universitas Al-Qolam Malang, 2024)
At the age of 11-17 years, teenagers generally experience development to reach physical, mental, social and emotional maturity. When self-control is not yet perfect, they are faced with the challenges of puberty, changes in social roles and the environment in an effort to achieve independence according to their age. If you cannot overcome this, problems will arise in the form of social deviations such as aggressive behavior, excessive fear, apathy and self-harming behavior. This research is to determine the description of emotional and behavioral problems among students at SMPI Bhumi Ngasor Bakalan Malang. Schools that also have an Islamic boarding school background will undergo initial screening to detect emotional and behavioral disorders. This type of research is descriptive observation quantitative research. The tool used to assess mental and emotional problems is the SDQ (Strength and Difficulties Questionnaire). As a result, the emotional and behavioral disorders of 33 SMPI Bhumi Ngasor students had overall scores in the abnormal category (39.4%) followed by the borderline category (36.4%). Male students experience more emotional disturbances than female students. Apart from that, for behavior and peer problems, both are in the borderline or borderline category. The normal category is in the emotional, hyperactivity and pro-social dimensions. Key words: Emotional and Behavioral Problems; Teenagers; Strength and Difficulties Questionnaire